Current-mode third-order quadrature oscillator using VDTAs and grounded capacitors - Phatsornsiri, Punnavich; Lamun, Panit; Kumngern, Montree; Torteanchai, Usa (My University, 2014)
This paper presents a novel electronically tunable current-mode third-order quadrature oscillator based on voltage differencing transconductance amplifier (VDTA). The proposed oscillator is constructed using two VDTAs and three grounded capacitors, which is advantageous for integrated circuit implementation. The circuit provides two current outputs with 90° phase difference from high output impedance terminals. The condition of oscillation and the frequency of oscillation can be electronically tuned by adjusting the bias current of the VDTAs. The sensitivity studies of the circuit have been carried out. PSPICE simulations with 0.35 μm TSMC CMOS process parameters are given to confirm the theoretical analysis. © 2014 IEEE.
Keywords: current-mode circuit; quadrature oscillator; Voltage Differencing Transconductance Amplifier (VDTA)